Russian School Textbooks on Religion: Theological Learning, Ideological Confrontation, or Religious Education - Basil, John D. (A journal of church and state, 2013)
In the autumn of 2002, signs of an important disagreement began to appear in the Russian media. They arose in the form of pro and con newspaper articles publish